Development of Electronic Modules Based on Blended Learning Flipped Classroom in Arabic Language Subject Class X Nuraida Islamic Boarding School Bogor - Penta Eka Nova Rinda; Nurdin Ibrahim; Masitowati Gatot (Indonesian Journal for Islamic Studies, 2024)
Learning outcomes in Arabic language subjects in secondary schools are still low, so effective teaching materials are needed to improve Arabic language learning outcomes. The study aims to develop and test the feasibility and effectiveness of developing electronic modules based on blended learning flipped classroom in class X Arabic subjects at Nuraida Islamic Boarding School Bogor. The study uses a development model Borg and Gall which is integrated with the Rowntree model. To test the feasibility of the researcher using validation from media experts, design experts and material experts and also considering the results of user responses from teachers and students. From the results of the feasibility test carried out by material experts at 81.33%, instructional design/media experts at 90%, teacher users at 90% and student users at 95%. Overall, the category was "very feasible". The results of the pretest and posttest data analysis show that the average pretest score of students is 52 and the average posttest score of students is 90, while the maximum average score is 70. Based on effectiveness testing using the N-Gain Score formula, a result of 0.8 was obtained in the high category or a percentage of 90. Per the conversion of the achievement level of the N-Gain score review results with a value of >76 which is categorized as effective. This means that the e-module developed is effective in improving student learning outcomes in Arabic language subjects. So, it can be concluded that the electronic module based on the blended learning flipped classroom in Arabic subjects that was developed is feasible and effective to use.